Implementation Of Halal Tourism In Central Aceh: Application Of The Global Muslim Travel Index - Nicko Rizky, Glah Rami; Sartiyah, Sartiyah; Ramadhani, Evi (BISNIS, 2023)
This research aims to find out the tourism industry follows the GMTI factor in the implementation of halal tourism in Central Aceh, and know the important factors of GMTI in implementing halal tourism in Central Aceh. The data used in this study is Primary data, which is 100 tourism industry businesses, namely lodging, culinary, and tourist attractions. The results obtained from this study, services have a positive effect on the implementation of halal tourism, while access, communication, and the environment have not affected the implementation of halal tourism in Central Aceh regency. Tourism services have a great opportunity for the implementation of halal tourism in Central Aceh. Access, communication, and the environment have not affected the implementation of halal tourism.